ENERGY EXPENDITURE IN PRESCHOOL CHILDREN DEPENDING ON VARIOUS TEACHING METHODS WHEN PRACTICING THE ABC GYMNASTICS PROGRAMME - Mateja Videmšek; Tjaša Logaj; Gregor Starc; Vedrana Sember; Damir Karpljuk; Ana Šuštaršič (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
The aim of the study was to determine whether obstacle course and circuit training are efficient teaching methods as forms of exercise in terms of their intensity, monitored by using energy expenditure measuring devices. The key differences in energy expenditure between the two teaching methods were examined. The BodyMedia SenseWear equipment for measuring energy expenditure was used to acquire data from two practice sessions. A sample of participants included 24 five-year-old children from one kindergarten in Ljubljana, although complete data from both afternoon practice sessions was obtained only from 12 children. The study has shown that obstacle course and circuit training are adequate teaching methods, as moderate to vigorous intensity was achieved with both methods when practicing the ABCs of gymnastics. The average energy expenditure has exceeded 7 MET in the main part of two practice sessions for both obstacle course and circuit training. The results showed no statistically significant differences in energy expenditure between genders or the specific teaching method used.